2010
DOI: 10.1007/s11886-010-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance in Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy is a fascinating and complex disorder with substantial variability in phenotypic expression and natural progression. Recently, there has been substantial research demonstrating incremental utility of cardiac magnetic resonance in the diagnosis and treatment of this disease. With the increasing utilization of multimodality imaging, our understanding of the subtle morphologic differences and their prognostic implications is only going to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The high temporal and spatial resolution of CMR with superior intrinsic contrast allows more precise evaluation of myocardial morphology and reproducible quantitative assessment of ventricular volumes and function. [26][27][28][29] We found that patients with MYBPC3 variants were more likely to have impaired ventricular function compared to patients with MYH7 variants and had a trend towards an increase in arrhythmic events, with a higher proportion of patients receiving ICDs. Finally, we found that LGE burden was higher in patients with identifiable gene variants.…”
Section: Discussionmentioning
confidence: 67%
“…The high temporal and spatial resolution of CMR with superior intrinsic contrast allows more precise evaluation of myocardial morphology and reproducible quantitative assessment of ventricular volumes and function. [26][27][28][29] We found that patients with MYBPC3 variants were more likely to have impaired ventricular function compared to patients with MYH7 variants and had a trend towards an increase in arrhythmic events, with a higher proportion of patients receiving ICDs. Finally, we found that LGE burden was higher in patients with identifiable gene variants.…”
Section: Discussionmentioning
confidence: 67%